Find the maximal value of k , such that for all sets of positive real triples ( a , b , c ) ,
a + b + c + 3 3 a b c ≥ k ( a b + b c + c a ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Your Iogic was wrong...
This is the OP's solution.
As with all such inequality problems, the first step is to guess a value of k then prove it. Normally the maximum occurs when all the variables are equal, i.e. a = b = c , and here we have 6 ≥ 3 k ↔ k ≤ 2 . Now we will prove that:
a + b + c + 3 3 a b c ≥ 2 ( a b + b c + c a )
Now, motivated by the fact that we let a = b = c , we can try to smooth the variables till they are equal. See here for more about the principle of smoothing. Basically, suppose WLOG that a ≤ b ≤ c and also let f ( a , b , c ) = a + b + c + 3 3 a b c − 2 ( a b + b c + c a ) . Now, we use a change of variables, as follows:
a 1 = a , b = b 1 = c 1 = b c = j
Then we will have:
f ( a 1 , b 1 , c 1 ) = ( a + 2 c + 3 × a 3 1 × j 3 2 ) − 2 [ j + ( 2 a j ) 2 1 ]
= a + 3 × a 3 1 × j 3 2 − 4 ( a j ) 2 1 ≥ 0
Where the equality holds iff a = 0 or a = b = c .
By the smoothing principle, let us prove that f ( a , b , c ) ≥ f ( a 1 , b 1 , c 1 ) . Remark first that
f ( a , b , c ) − f ( a 1 , b 1 , c 1 ) = b + c − 2 a 2 1 ( b 2 1 + c 2 1 − 2 j 2 1 ) − 2 j
Because we have: a ≤ j , b 2 1 + c 2 1 ≥ 2 j 2 1 , thus we can conclude that:
f ( a , b , c ) − f ( a 1 , b 1 , c 1 ) ≥ b + c − 2 j ( b + c − 2 j ) − 2 j
= b + c − 2 ( b + c ) j + 2 j
= ( b − j ) 2 + ( c − j ) 2
≥ 0
This basically implies that f ( a , b , c ) ≥ 0 as desired. ■
we can use schur inequality
BTW, the intermediate inequality f ( a 1 , b 1 , c 1 ) ≥ 0 holds by AM-GM.
Lets take a=b=c. K will be 2.
Let a , b , and c all be equal to 1. Thus for the equation to be set perfectly equal, k = 2 .
Simplifying first the inequality by dividing both sides by 3: (a+b+c)/3 + cube root (abc) is greater than or equal to k(sqrt (ab) + sqrt (bc) + sqrt (ac))/3.
One can see that AM - GM Inequality is the best tool for this problem. This implies that
(a+b+c)/3 is greater than or equal to cube root(abc)
and
(sqrt (ab) + sqrt (bc) + sqrt (ac))/3 is greater than or equal to cube root (abc)
Multiplying the second applied AM - GM inequality both sides by k.
k(sqrt (ab) + sqrt (bc) + sqrt (ac))/3 is greater than or equal to k cube root (abc).
Using properties of inequality:
[(a+b+c) - k(sqrt (ab) + sqrt (bc) + sqrt (ac))]/3 + cube root (abc) is greater than or equal to 0. [(a+b+c) - k(sqrt (ab) + sqrt (bc) + sqrt (ac))]/3 is greater than or equal to - cube root (abc).
Remember from the applied AM - GM Inequality that: k(sqrt (ab) + sqrt (bc) + sqrt (ac))/3 is greater than or equal to k cube root (abc).
Hence, [(a+b+c) - k(sqrt (ab) + sqrt (bc) + sqrt (ac))]/3 is greater than or equal to (1-k) cube root (abc).
Comparing the yielded inequality to the the given has the same left-hand side but the right-hand side does not. This inequality satisfies when 1-k = -1. Hence, k = 2 and this is the maximum value that makes this inequality true.
Problem Loading...
Note Loading...
Set Loading...
We know that
a + b + c ≥ a b + b c + c a and the equality holds when a = b = c
a + b + c ≥ 3 3 a b c and the equality holds when a = b = c
So, when a = b = c , we have
3 3 a b c = a b + b c + c a
This lead to
a + b + c + 3 3 a b c ≥ 2 ( a b + b c + c a )
Hence, k = 2